PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA MELALUI SEMANGAT KERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BARRU - Rusdi Rusdi; Maryadi Maryadi; Muhammad Idris (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The research aims to determine and analyze (1) the direct effect of compensation and work discipline on employee morale at the Barru District Public Works and Spatial Planning Agency (2) the direct effect of compensation, work discipline and morale on employee performance at the Public Works and Spatial Planning Office Barru Regency (3) the direct effect of compensation and work discipline on performance through employee morale at the Public Works and Spatial Planning Office of Barru Regency (4) The indirect influence of work competency and discipline on performance through employee morale at the Public Works and Spatial Planning Services District Barru. This research design uses survey research.. The population in this study included all employees of the Public Works and Spatial Planning Office in Barru Regency, amounting to 81 people. Sampling of this study was conducted by using a saturated sampling technique (census), which determines the entire population to be sampled as many as 81 employees of the Department of Public Works and Spatial Planning in Barru District. The data analysis technique used is path analysis. The results showed that (1) there was a direct positive effect on compensation and work discipline on employee morale at the Public Works and Spatial Planning Office in Barru District (2) there was a direct positive effect on compensation, work discipline and morale on employee performance at the Department of Work General and Spatial Planning of Barru Regency (3) there is a direct positive effect on compensation and work discipline through employee morale at the Barru District Public Works and Spatial Planning (4) there is an indirect positive effect on competence and work discipline on performance through employee morale at the Barru District Public Works and Spatial Planning Office.